The courtship eaudiobook - Burrowes, Grace (Windham, 2015)
Percival Windham is a second son and a cavalry officer acclaimed and respected by his men. He is immensely attractive and distracts himself with the women who seem to throw themselves at him at every turn. At a country house party, Percy meets beautiful, retiring Esther Himmelfarb. Esther's wealthier relations are taking shameless advantage of her dependence on them, and only Percy seems to see the striking intelligence beneath her modest demeanor. Percy sees her as the perfect companion, and she finds in him the man of her dreams.